Rapid adsorption of selenium removal using iron manganese-based micro adsorbent - Sundus Saeed Qureshi; Sheeraz Ahmed Memon; Rafi-ul-Zaman; Nanik Ram; Sumbul Saeed; Nabisab Mujawar Mubarak; Rama Rao Karri (Scientific Reports)
Abstract Selenium in wastewater is of particular concern due to its increasing concentration, high mobility in water, and toxicity to organisms; therefore, this study was carried out to determine the removal efficiency of selenium using iron and manganese-based bimetallic micro-composite adsorbents. The bimetallic micro-composite adsorbent was synthesized by using the chemical reduction method. Micro-particles were characterized by using energy-dispersive X-ray spectroscopy for elemental analysis after adsorption, which confirms the adsorption of selenium on the surface of the micro-composite adsorbent, scanning electron microscopy, which shows particles are circular in shape and irregular in size, Brunauer–Emmett–Teller which results from the total surface area of particles were 59.345m2/g, Zeta particle size, which results from average particles size were 39.8 nm. Then it was applied to remove selenium ions in an aqueous system. The data revealed that the optimum conditions for the highest removal (95.6%) of selenium were observed at pH 8.5, adsorbent dosage of 25 mg, and contact time of 60 min, respectively, with the initial concentration of 1 ppm. The Langmuir and Freundlich isotherm models match the experimental data very well. The results proved that bimetallic micro-composite could be used as an effective selenium adsorbent due to the high adsorption capacity and the short adsorption time needed to achieve equilibrium. Regarding the reusability of bimetallic absorbent, the adsorption and desorption percentages decreased from 50 to 45% and from 56 to 53%, respectively, from the 1st to the 3rd cycle.